Responsive feeding ibu dan asupan makan anak stunting usia 2-5 tahun - Larasati, Adisti Qamahadlina; Sudargo, Toto; Susetyowati, Susetyowati (Jurnal Gizi Klinik Indonesia, 2022)
Maternal responsive feeding and food intake of 2-5 years old stunted childrenBackground: Inadequate food intake is one of the stunting determinants in children. Responsive feeding is related to children's food intake.Objective: This study aimed to determine the relation between maternal responsive feeding and food intake of stunting children aged 2-5 years.Methods: This study was a cross-sectional study with 92 mothers who had stunted children aged 2-5 years were participated. Responsive feeding was measured by a validated RFPAT questionnaire, and food intake was measured by 2x24 hour recall. Data were analysed using Spearman correlation test (p<0.05).Results: 52.2% of mothers had bad responsive feeding practices. Most children did not meet 80% of their energy, carbohydrate, and fat needs according to the RDA standards, but the majority of children (92.5%) met more than 80% of their protein needs. There is no statistically significant relationship between maternal responsive feeding and the stunting child's food intake.Conclusion: There is no significant relationship between responsive feeding of mothers and food intake of stunting children. It is necessary to conduct other more in-depth research related to the interaction of mother and child when eating, proper child feeding practices, and its relationship with children's food intake.